Chile´s economic performance in the 20th Century, a comparative perspective - Hofman, Andre (Estudios de Economía, 2016)
This article aims to assess Chile’s economic performance in the 20th century in a comparative perspective. The casual analysis of economic performance is conducted at two levels, “ultimate” and “proximate”. Ultimate causes refer to institutions, ideologies pressure groups, historical accidents and economic policy at the national level, while involving incluences, either positive or negative, from outside the country it is difficult to quantify these “ultimate” features and legitimate scope for disagreement on what is important remains is the case in Chile. Quantification becomes possible in the case of “proximate” causes of the economic performance and it is here where all kind of models have been developed. One strand of measures are comparative macroeconomic growth accounts which provide significant insights in tryng to “explain” GDP growth (per capita) and productivity by measuring inputs of labor and capital, availability of natural resources and influences affecting the efficiency with which resources are combined. In this article emphasis is given to “proximate” causes of growth through quantitative supply-side analysis, but “ultimate” causes and especially the role of policy and institutions, both national and international, in economic performance are also analyzed. The study includes seven Latin America countries to compare Chilean and Latin American performance to that of a) three Asian developing countries, b) Portugal and Spain and c) six advanced countries which display levels of income and productivity among the highest in the world.